Film, laminate, and optical member

The use of a resin composition with silica fine particles, an alkoxysilane hydrolyzed condensate, and a hydrophilic resin with a high melting point in porous silicon oxide films addresses the issues of dicing defects and refractive index achievement, resulting in improved dicing properties and optical performance.

JP2025047769APending Publication Date: 2025-04-03MITSUBISHI CHEM CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023156466
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-21
Publication Date
2025-04-03

AI Technical Summary

Technical Problem

Porous silicon oxide films laminated on substrates often suffer from defects during dicing and fail to achieve the desired refractive index.

Method used

A resin composition comprising a 1.5 to 10 μm thick film with silica fine particles, an alkoxysilane hydrolyzed condensate, and a hydrophilic resin with a melting point of 80° C. or higher, which suppresses defects during dicing and maintains a desired refractive index.

Benefits of technology

The film exhibits excellent dicing properties and maintains a stable desired refractive index, improving flexibility and adhesion to the substrate while reducing haze and enhancing optical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025047769000001
    Figure 2025047769000001
  • Figure 2025047769000002
    Figure 2025047769000002
  • Figure 2025047769000003
    Figure 2025047769000003
Patent Text Reader

Abstract

To provide a film which suppresses occurrence of defects when a thick film is diced and has a desired refractive index.SOLUTION: A film has thickness of 1.5 to 10 μm, and is composed of a resin composition containing silica fine particles, an alkoxysilane hydrolysis condensate and a hydrophilic resin having a melting point of 80°C or higher.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a film, a laminate, and an optical member. [Background technology]

[0002] Porous silicon oxide films have a wide range of industrial applications due to their low refractive index, transparency, electrical insulation, etc. In particular, applications that utilize their low refractive index include anti-reflective coatings for electronic device displays, automobile panels, lighting fixtures, solar power devices, camera lenses, face shields, and glasses, optical waveguides, and cladding layers for optical fibers.

[0003] For example, Patent Document 1 discloses a method for producing a binder liquid for forming a silicon oxide thin film, which is suitable for forming a porous silicon oxide thin film with excellent adhesion to a substrate. Also, a method for producing a coating liquid for forming a silicon oxide thin film has been proposed, in which a hydrolyzable silane compound is subjected to hydrolysis and condensation reaction, and the reaction product is mixed with silica fine particles to form a binder liquid for forming a silicon oxide thin film. Moreover, Patent Document 2 proposes a porous silicon oxide film with excellent antifogging properties. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2019-23269 A [Patent Document 2] JP 2021-182134 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, even when the porous silicon oxide films described in Patent Documents 1 and 2 are laminated on a substrate, defects may occur during dicing, and the desired refractive index may not be achieved. The present invention has been made in consideration of the above problems, and aims to provide a film having a desired refractive index that suppresses the occurrence of defects during dicing of a thick film, and a laminate and optical component in which such films are stacked. [Means for solving the problem]

[0006] As a result of intensive research into solving the above problems, the present inventors have found that a film having a thickness of 1.5 to 10 μm made of a resin composition containing silica fine particles, an alkoxysilane hydrolysis condensate, and a hydrophilic resin having a melting point of 80° C. or higher can suppress defects during dicing of a thick film and has a desired refractive index, thereby completing the present invention.

[0007] That is, the gist of the present invention is as follows.

[0008] <1> A film having a thickness of 1.5 to 10 μm, which is made of a resin composition containing silica fine particles, an alkoxysilane hydrolysis condensate, and a hydrophilic resin having a melting point of 80° C. or higher. <2> The hydrophilic resin has a hydroxyl group. <1> The membrane according to claim 1. <3> The content of hydroxyl groups directly bonded to the main chain of the hydrophilic resin is 35 mol % or less. <2> The membrane according to claim 1. <4> The silica fine particles are chain-like silica fine particles. <1> ~ <3> 2. The membrane according to claim 1 . <5> The average primary particle diameter of the silica fine particles is 5 to 100 nm. <1> ~ <4> 2. The membrane according to any one of claims 1 to 11. <6> The weight average molecular weight of the alkoxysilane hydrolysis condensate is 1,000 to 5,000. <1> ~ <5> 2. The membrane according to claim 1 . <7> The average polymerization degree of the hydrophilic resin is 200 to 2,000. <1> ~ <6> 2. The membrane according to claim 1 . <8> The hydrophilic resin is a polyvinyl alcohol resin. <1> ~ <7> 2. The membrane according to claim 1 . <9> The content of the hydrophilic resin is more than 1 part by mass per 100 parts by mass of the silica fine particles and the alkoxysilane hydrolysis condensate. <1> ~ <8> 2. The membrane according to claim 1 . <10> The content of the alkoxysilane hydrolysis condensate is 5 to 30 parts by mass based on 100 parts by mass of the resin composition. <1> ~ <9> 2. The membrane according to claim 1 . <11> The content of the silica fine particles is 60 to 90 parts by mass based on 100 parts by mass of the resin composition. <1> ~ <10> 2. The membrane according to claim 1 . <12> The porosity is 10 to 80%. <1> ~ <11> 2. The membrane according to claim 1 . <13> The refractive index is 1.15 to 1.40. <1> ~ <12> 2. The membrane according to claim 1 . <14> The pore size is 0.1 to 50 nm. <1> ~ <13> 2. The membrane according to claim 1 . <15> The above <1> ~ <14> A laminate comprising the film according to any one of the preceding claims and a substrate. <16> The substrate is made of glass. <15> The laminate according to claim 1. <17> The above <16> An optical member comprising the laminate according to claim 1. Effect of the Invention

[0009] The film of the present invention has excellent dicing properties even when it is a thick film, and can stably maintain a desired refractive index. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The film, laminate, and optical component according to the present invention will be described in detail below with reference to their embodiments. However, the present invention is not limited to the following description, and can be modified as appropriate within the scope of the present invention, other than the examples given below.

[0011] In this specification, the use of "to" means that the numerical values ​​before and after it are included as the lower limit and upper limit.

[0012] The film of the present invention has a thickness of 1.5 to 10 μm and contains silica fine particles, an alkoxysilane hydrolysis condensate, and a hydrophilic resin having a melting point or solidification point of 80° C. or higher. The film of the present invention can be produced using the resin composition used in the present invention.

[0013] [Resin composition] The components of the resin composition used in the present invention are described in detail below. The resin composition used in the present invention contains silica fine particles, an alkoxysilane hydrolysis condensate, and a hydrophilic resin. When the resin composition used in the present invention is prepared for coating, it may be made fluid by appropriately adding a solvent or the like.

[0014] A film can be produced by molding the resin composition used in the present invention. A laminate can be obtained by laminating the film on a substrate. This improves the flexibility of the film, for example, and suppresses cracking and peeling when a laminate of thick films is diced to fit the product size. A film having excellent adhesion and flexibility to the substrate and a refractive index excellent for optical applications can be obtained.

[0015] [Silica particles] The resin composition used in the film of the present invention contains silica fine particles. The average primary particle diameter of the silica fine particles is preferably 5 to 100 nm. When the average primary particle diameter is 5 nm or more, the volume of the voids between the fine particles can be increased, and the refractive index can be reduced. The average primary particle diameter of the silica fine particles is more preferably 6 nm or more, and more preferably 7 nm or more. On the other hand, when it is 100 nm or less, the roughness of the film surface and light scattering can be reduced, and haze can be reduced. The average primary particle diameter of the silica fine particles is more preferably 50 nm or less, and particularly preferably 30 nm or less.

[0016] Here, the shape of the silica fine particles can be observed using an electron microscope (SEM, etc.). The average primary particle size is usually determined by the specific surface area (m 2The average length is a value given by the formula: average primary particle size = (2720 / specific surface area) from the specific surface area (g). The average length can be measured by dynamic light scattering.

[0017] The silica fine particles are not particularly limited, and may be either aggregated silica fine particles or non-aggregated silica fine particles. For example, the aggregated silica fine particles may be chain-like silica fine particles having an average primary particle diameter of 5 to 100 nm. In addition, the non-aggregated silica fine particles may be at least one of non-aggregated silica fine particles having an average primary particle diameter of 5 to 100 nm and hollow non-aggregated silica fine particles having an average primary particle diameter of 10 to 100 nm. These are appropriately selected depending on the purpose of the film to be formed. The silica fine particles are preferably chain-like silica fine particles from the viewpoints of dicing property when the film is thick and the refractive index of the film.

[0018] [Chain-like silica particles] Chain silica fine particles refer to a continuous chain of multiple primary particles that are directly bonded to each other by chemical bonds such as siloxane bonds without any joints made of other materials. They may be linearly extended or two-dimensionally or three-dimensionally curved. In addition, the chain silica fine particles are preferably continuous silica fine particles having an average primary particle diameter of about 5 to 30 nm and an average length of about 30 to 200 nm.

[0019] In the deposition state, such chain silica fine particles have large interparticle voids, so that the refractive index of the film can be reduced.On the other hand, when silica fine particles other than chain silica fine particles, for example, only spherical silica fine particles are used, in order to reduce the refractive index, it is necessary to mix a large amount of spherical silica fine particles.In this case, the content ratio of matrix structure other than spherical silica fine particles becomes small, so that haze increases and the appearance may be significantly deteriorated.In the present invention, by using chain silica fine particles, it is easy to achieve both low refractive index and excellent appearance.

[0020] The average primary particle diameter of the chain silica fine particles is preferably 6 nm or more, more preferably 7 nm or more. By making the average primary particle diameter of the chain silica fine particles 6 nm or more, the refractive index of the film can be reduced. On the other hand, the average primary particle diameter of the chain silica fine particles is preferably 100 nm or less, preferably 50 nm or less, more preferably 30 nm or less. By making the average primary particle diameter of the chain silica fine particles 100 nm or less, a film of a desired film thickness can be easily formed, and the roughness of the film surface and light scattering can be reduced, and haze can be reduced.

[0021] Specific examples of chain silica particles include Nissan Chemical Industries, Ltd.'s "Snowtex (registered trademark)-OUP" (average length: 40 to 100 nm), "Snowtex (registered trademark)-UP" (average length: 40 to 100 nm), "Snowtex (registered trademark) PS-M" (average length: 80 to 150 nm), "Snowtex (registered trademark) PS-MO" (average length: 80 to 150 nm), "Snowtex (registered trademark) PS-S" (average length: 80 to 120 nm), "Snowtex (registered trademark) PS-SO" (average length: 80 to 120 nm), "IPA-ST-UP" (average length: 40 to 100 nm), "MEK-ST-UP" (average length: 40 to 100 nm), "PGME-ST-UP" (average length: 40 to 100 nm), and colloidal silica such as "Fine Cataloid F-120" manufactured by JGC Catalysts and Chemicals Industries, Ltd. If necessary, it may be preferable to use a solvent-substituted product. Known commercially available dispersion media include methyl ethyl ketone, methyl isobutyl ketone, propylene glycol monomethyl ether, and propylene glycol monomethyl ether acetate. These dispersion media can be appropriately changed to other components depending on the application.

[0022] The content of the silica fine particles is preferably 60 to 90 parts by mass relative to 100 parts by mass of the resin composition used in the present invention. More preferably, the content of the silica fine particles is preferably 60 to 90 parts by mass as a ratio ("mass of silica fine particles" / "mass of silica fine particles + mass of alkoxysilane hydrolysis condensate + mass of hydrophilic resin") relative to 100 parts by mass of the total of the silica fine particles, alkoxysilane hydrolysis condensate, and hydrophilic resin contained in the resin composition. When the content of the silica fine particles is 60 parts by mass or more relative to 100 parts by mass of the resin composition used in the present invention, the porosity in the film increases, so that the refractive index can be reduced. The content of the silica fine particles is more preferably 65 parts by mass or more, and particularly preferably 70 parts by mass or more, relative to 100 parts by mass of the resin composition used in the present invention. On the other hand, when the content is 90 parts by mass or less, the adhesion to the substrate and the mechanical strength of the film are further improved. The content of the silica fine particles is more preferably 85 parts by mass or less, particularly preferably 80 parts by mass or less, based on 100 parts by mass of the resin composition used in the present invention.

[0023] [Alkoxysilane hydrolysis condensation product] The alkoxysilane hydrolysis condensate contained in the resin composition used in the present invention is a compound having a siloxane bond, and is a compound obtained by hydrolysis condensation of an alkoxysilane. The method for producing the alkoxysilane hydrolysis condensate is not particularly limited, but it is composed of a hydrolyzable silane compound or a multimer of a hydrolyzable silane compound, and is usually produced using water and an organic solvent. The composition produced from this hydrolyzable silane compound or a multimer of a hydrolyzable silane compound, water, and an organic solvent is called a silicate oligomer, and as described later, a coating liquid (coating liquid for film formation) is produced, for example, by adding silica fine particles and a hydrophilic resin to this silicate oligomer.

[0024] The weight-average molecular weight of the alkoxysilane hydrolysis condensate of the present invention is preferably 1,000 to 5,000. If the weight-average molecular weight of the alkoxysilane hydrolysis condensate is 1,000 or more, the silicate oligomer containing the alkoxysilane hydrolysis condensate is less likely to gel, and the storage stability is improved. It is more preferably 1,500 or more, and particularly preferably 1,800 or more. If it is 5,000 or less, the adhesion to the substrate is improved, and cracking and peeling during dicing of a thick film are suppressed. It is more preferably 4,000 or less, and particularly preferably 3,000 or less. Such a weight-average molecular weight corresponds to a polymer having an average degree of polymerization n of 2 to 100.

[0025] The weight average molecular weight is a value measured by gel permeation chromatography (GPC) under the following conditions. Solvent: Tetrahydrofuran Equipment name: TOSOH HLC-8220GPC Column: TOSOH TSKgel Super HM-N (2 columns) and HZ1000 (1 column) connected together Column temperature: 40℃ Sample concentration: 0.01% by mass Flow rate: 0.6ml / min Calibration curve: PEG (a 4-point cubic approximation calibration curve with molecular weights of 20,000, 4,000, 1,000, and 200 was used)

[0026] The concentration of the alkoxysilane hydrolysis condensate in the silicate oligomer is preferably 15% by mass or less, more preferably 12% by mass or less, and particularly preferably 10% by mass or less. When the concentration of the alkoxysilane hydrolysis condensate is 15% by mass or less, the stability of the solution is improved, and the dispersibility when mixed with silica fine particles is further improved. On the other hand, from the viewpoint of the shape efficiency of the film, the concentration of the alkoxysilane hydrolysis condensate in the silicate oligomer is preferably 0.1% by mass or more, more preferably 0.2% by mass or more. Such a silicate oligomer is transparent, and the turbidity measured using a kaolin turbidimeter is usually 10 or less.

[0027] The organic solvent contained in the silicate oligomer is preferably a hydrophilic solvent. The hydrophilic solvent is not particularly limited, but generally, alcohols such as methanol, ethanol, propanol, butanol, cellosolves such as ethyl cellosolve, butyl cellosolve, propyl cellosolve, glycols such as ethylene glycol, propylene glycol, hexylene glycol, etc. are used. These solvents may be used alone or in combination of two or more. The content of the organic solvent in the silicate oligomer is not particularly limited, but is usually 40% by mass to 99% by mass.

[0028] The hydrolyzable silane compound is a silane compound having a hydrolyzable group such as an alkoxy group, an alkoxyalkoxy group, an acyloxy group, an aryloxy group, an aminoxy group, an amide group, a ketoxime group, an isocyanate group, a halogen atom, etc. As the hydrolyzable silane compound, those having one to four functionalities depending on the number of hydrolyzable groups are known.

[0029] In the present invention, an alkoxysilane compound is preferably used as the hydrolyzable silane compound. Examples of the alkyl group of the alkoxy group (-OR) include lower alkyl groups such as methyl, ethyl, propyl, and butyl.

[0030] Representative examples of alkoxysilane compounds include dimethyldimethoxysilane (DMDMS), methyltrimethoxysilane (MTMS), tetramethoxysilane (TMOS), dimethyldiethoxysilane (DMDES), methyltriethoxysilane (MTES), tetraethoxysilane (TEOS), etc. Commercially available dimethyldimethoxysilane (DMDMS) is usually a solution with a purity of 99% by mass.

[0031] The polymer of hydrolyzable silane compound is polymerized (oligomerized) by condensation of the monomers mentioned above. In this reaction, first, silanol group (-Si-OH) is formed by hydrolysis of alkoxy group. At the same time, alcohol (R-OH) is generated. Next, siloxane bond (-Si-O-Si-O-) is formed by (dehydration) condensation of silanol group, and this condensation is repeated to form siloxane oligomer.

[0032] The polymer structure may be linear, branched, cyclic, or network-like. If a tetraalkoxysilane polymer has a linear structure, it is represented by the following general formula (I). RO(Si(OR)2O) n R (I)

[0033] In the general formula (I), R is an alkyl group, and n represents the degree of polymerization of the polymer. Usually available polymers are compositions of polymers with different n, and therefore have a molecular weight distribution. The degree of polymerization is represented by the average n. As the polymer of the alkoxysilane compound, from the viewpoint of hydrolyzability and condensability of the alkoxy group, a polymer of tetramethoxysilane in which R is a methyl group or a polymer of tetraethoxysilane in which R is an ethyl group is preferred.

[0034] The degree of polymerization of tetrafunctional hydrolyzable silane compounds such as tetraalkoxysilanes or their polymers is sometimes expressed as "silica content". "Silica content" is the mass ratio of silica (SiO2) generated from the compound, and is obtained by stably hydrolyzing the compound, calcining it, and measuring the amount of silica generated. "Silica content" also indicates the ratio of silica generated per molecule of the compound, and is a value calculated by the following general formula (II). Silica content (parts by mass) = degree of polymerization × molecular weight of SiO2 / molecular weight of the compound (II)

[0035] In the present invention, a polymer having a degree of polymerization n of usually 2 to 100, preferably 2 to 70, more preferably 2 to 50 is used. It is convenient to use a commercially available product as such a polymer. As the degree of polymerization n increases, the molecular weight of the alkoxysilane hydrolysis condensate produced increases, the molecular weight distribution becomes broad, and the viscosity increases.

[0036] Commercially available polymers of hydrolyzable silane compounds include MKC Silicate MS51, MKC Silicate MS56, MKC Silicate MS57, and MKC Silicate MS56S (all of which are polymers of tetramethoxysilane) manufactured by Mitsubishi Chemical Corporation, Methyl Silicate 51 (a polymer of tetramethoxysilane), Methyl Silicate 53A, Ethyl Silicate 40, and Ethyl Silicate 48 manufactured by Colcoat Co., Ltd., and Ethyl Silicate 40 and Silicate 45 (all of which are polymers of tetraethoxysilane) manufactured by Tama Chemicals Co., Ltd.

[0037] The alkoxysilane hydrolysis condensate of the present invention is preferably produced using a hydrolyzable silane composition that contains a bifunctional hydrolyzable silane compound and a polymer of the hydrolyzable silane compound, and the content of the polymer of the hydrolyzable silane compound is 50% by mass or more. The ratio of the polymer in the hydrolyzable silane composition is preferably 70% by mass or more. If the ratio of the polymer in the hydrolyzable silane composition is 70% by mass or more, a branched, cyclic, or network structure is appropriately formed in the reaction composition, and the adhesion between the film and the substrate is further improved. It is more preferably 75% by mass or more. On the other hand, the proportion of polymers in the hydrolyzable silane composition is preferably 90% by mass or less. If the proportion of polymers in the hydrolyzable silane composition is 90% by mass or less, gelation is less likely to occur and storage stability is improved. In addition, the ratio of the difunctional hydrolyzable silane compound, which is a monomer in the hydrolyzable silane composition, is preferably 10% by mass or more and 30% by mass or less. If the ratio of the difunctional hydrolyzable silane compound is 10% by mass or more, the silicate oligomer containing the obtained alkoxysilane hydrolysis condensate is less likely to gel and has better storage stability. On the other hand, if the ratio is 30% by mass or less, the coating property during film formation is better. This ratio is more preferably 25% by mass or less.

[0038] The conditions for the hydrolysis and condensation reaction are preferably those described in JP 2021-182134 A. This reaction is carried out by continuously dropping an aqueous acid catalyst solution into a hydrophilic solvent solution in which the hydrolyzable silane composition is dissolved under stirring conditions.

[0039] The content of the alkoxysilane hydrolysis condensate is preferably 5 to 30 parts by mass relative to 100 parts by mass of the resin composition used in the present invention. More preferably, the content of the alkoxysilane hydrolysis condensate is preferably 5 to 30 parts by mass as a ratio ("mass of alkoxysilane hydrolysis condensate" / "mass of silica fine particles + mass of alkoxysilane hydrolysis condensate + mass of hydrophilic resin") relative to 100 parts by mass of the total of the silica fine particles, the alkoxysilane hydrolysis condensate, and the hydrophilic resin contained in the resin composition. If the ratio of the alkoxysilane hydrolysis condensate is too low, the film formability of the film decreases, and if the ratio of the alkoxysilane hydrolysis condensate is too high, the refractive index of the film increases. The content of the alkoxysilane hydrolysis condensate is more preferably 5 to 25 parts by mass, and even more preferably 5 to 20 parts by mass relative to 100 parts by mass of the resin composition used in the present invention.

[0040] [Hydrophilic resin] The resin composition used in the present invention contains a hydrophilic resin. The hydrophilic resin preferably used in the present invention is one having a solubility of 5% by mass or more in water, methanol and ethanol. When the solubility is 5% by mass or more, the affinity with chain silica fine particles and alkoxysilane hydrolysis condensate is improved, the haze of the film is low, and the appearance is excellent. The solubility is preferably 8% by mass or more, and more preferably 10% by mass or more.

[0041] The resin composition of the present invention contains a hydrophilic resin having a melting point of 80°C or more. When producing the film of the present invention, after coating the liquid resin composition, drying is performed to remove the medium mixed appropriately. When this drying is performed, depending on the substrate, for example, drying is performed at about 120°C for a glass substrate, or at about 100°C for a thermoplastic resin substrate. During this drying, if the melting point or freezing point of the hydrophilic resin in the resin composition is lower than the drying temperature, the melted resin may enter the voids of the film, etc., and the desired refractive index may not be achieved. To suppress this, it is important that the melting point of the hydrophilic resin is such that it does not easily melt even at the drying temperature. As such a temperature, it has been found that if the melting point or freezing point is 80°C or more in consideration of the drying time, etc., the desired refractive index can be stably maintained. From the viewpoint of maintaining the desired refractive index, it is preferable that the resin composition of the present invention does not substantially contain a hydrophilic resin having a melting point of less than 80°C.

[0042] The melting point of the hydrophilic resin is a temperature measured by the visual inspection method according to JIS K6220. The melting point of the hydrophilic resin is more preferably 100° C. or higher, further preferably 120° C. or higher, and particularly preferably 130° C. or higher. There is no particular upper limit to the melting point of the hydrophilic resin, but it may be 300° C. or lower or 250° C. or lower.

[0043] The hydrophilic resin includes natural polymers, water-soluble resins, resin emulsions, etc. Examples of natural polymers that are hydrophilic resins include casein, soybean protein, starch, gelatin, etc.

[0044] Examples of water-soluble resins include polyvinyl alcohol resins (PVA), cellulose resins (methyl cellulose (MC), ethyl cellulose (EC), hydroxyethyl cellulose (HEC), carboxymethyl cellulose (CMC), etc.), chitins, and starch, which are resins having a hydroxyl group as a hydrophilic structural unit. Examples of resins having an ether bond include polyethylene oxide (PEO), polypropylene oxide (PPO), polyethylene glycol (PEG), and polyvinyl ether (PVE). Examples of resins having an amide group or amide bond include polyacrylamide (PAAM) and polyvinylpyrrolidone (PVP).

[0045] Examples of resin emulsions include conjugated diene polymer emulsions such as styrene-butadiene copolymers and methyl methacrylate-butadiene copolymers, acrylic polymer emulsions, vinyl polymer emulsions such as ethylene-vinyl acetate copolymers, ester polymer emulsions, urethane polymer emulsions, olefin polymer emulsions, epoxy polymer emulsions, and vinylidene chloride polymer emulsions.

[0046] The hydrophilic resin of the present invention preferably has a hydroxyl group. By having a hydroxyl group, the affinity with the chain silica fine particles and the alkoxysilane hydrolysis condensate is improved, and the haze of the film is reduced, resulting in a more excellent appearance. Examples of such hydrophilic resins include polyvinyl alcohol resins, cellulose resins (methyl cellulose (MC), ethyl cellulose (EC), hydroxyethyl cellulose (HEC), carboxymethyl cellulose (CMC), etc.), chitins, and starch.

[0047] The content of hydroxyl groups directly bonded to the main chain of the hydrophilic resin is preferably 35 mol % or less. When the content of hydroxyl groups is within the above range, the film-forming property, film flexibility, and dicing property of a thick film are good.

[0048] The above-mentioned hydroxyl group content is more preferably 32 mol% or less, more preferably 30.8 mol% or less, and even more preferably 30 mol% or less. On the other hand, the hydroxyl group content is preferably 5 mol% or more, more preferably 10 mol% or more, more preferably 11.6 mol% or more, even more preferably 15 mol% or more, and particularly preferably more than 17.8 mol%. By having a hydroxyl group content of 5 mol% or more, the haze of the film is low and the appearance is more excellent.

[0049] The content of hydroxyl groups is, for example, 1 It can be measured by H-NMR. In addition, when the hydrophilic resin is a vinyl alcohol resin, the content of the vinyl alcohol structural unit (hereinafter, corresponding to formula (1)) can be calculated from the saponification degree, and the content of the hydroxyl group in the vinyl alcohol structural unit can be calculated.

[0050] The content of the hydrophilic resin is preferably more than 1 part by mass as a ratio ("mass of hydrophilic resin" / "mass of silica fine particles + mass of alkoxysilane hydrolysis condensate") to 100 parts by mass of the total of silica fine particles and alkoxysilane hydrolysis condensate. When the content of the hydrophilic resin is in the above-mentioned range, the flexibility of the film and the dicing property of the thick film are good. The content of the hydrophilic resin is more preferably 1.5 parts by mass or more, further preferably 2.0 parts by mass or more, and particularly preferably 2.5 parts by mass or more. The upper limit is preferably 30 parts by mass or less, more preferably 25 parts by mass or less, and particularly preferably 20 parts by mass or less. When the content of the hydrophilic resin is 30 parts by mass or less, the haze of the film is low and the appearance is more excellent.

[0051] The content of the hydrophilic resin is preferably 5 to 30 parts by mass as a ratio ("mass of hydrophilic resin" / "mass of silica fine particles + mass of alkoxysilane hydrolysis condensate + mass of hydrophilic resin") to the total of 100 parts by mass of silica fine particles, alkoxysilane hydrolysis condensate, and hydrophilic resin. When the content of the hydrophilic resin is 5 parts by mass or more, the flexibility of the film and the dicing property of the thick film are good. More preferably, it is 8 parts by mass or more, and particularly preferably, it is 10 parts by mass or more. On the other hand, when the content is 30 parts by mass or less, the haze of the film is low and the appearance is more excellent. More preferably, it is 25 parts by mass or less, and particularly preferably, it is 20 parts by mass or less.

[0052] [Polyvinyl alcohol resin] The resin composition used in the present invention can suitably use a polyvinyl alcohol resin as a hydrophilic resin. The polyvinyl alcohol resin contained in the resin composition used in the present invention is not particularly limited in its specific structure as long as it is a resin having a vinyl alcohol structural unit represented by the following formula (1), and is typically obtained by saponifying a polyvinyl carboxylate obtained by polymerizing a vinyl carboxylate monomer such as vinyl acetate, but is not limited thereto.

[0053] [ka]

[0054] The polyvinyl alcohol resin may be an unmodified polyvinyl alcohol or a modified polyvinyl alcohol resin. The modified polyvinyl alcohol resin may be a copolymer modified polyvinyl alcohol resin synthesized by copolymerizing a monomer other than a vinyl ester monomer that provides a polyvinyl alcohol structural unit, or a modified polyvinyl alcohol resin obtained by synthesizing an unmodified polyvinyl alcohol and then modifying the main chain or side chain with an appropriate compound.

[0055] Examples of copolymerization monomers (unsaturated monomers) that can be used in copolymerized modified polyvinyl alcohol resins include olefins such as ethylene, propylene, isobutylene, α-octene, α-dodecene, and α-octadecene; hydroxyl group-containing α-olefins such as 3-buten-1-ol, 4-penten-1-ol, and 5-hexen-1-ol, as well as their acylated derivatives; unsaturated acids or salts thereof such as acrylic acid, methacrylic acid, crotonic acid, maleic acid, maleic anhydride, itaconic acid, and undecylenic acid; monoesters or dialkyl esters; diacetone acrylamide, acrylamide, methacrylic acid ... olefin sulfonic acids or their salts, such as ethylene sulfonic acid, allyl sulfonic acid, and methallyl sulfonic acid; quaternary ammonium salts, such as diallyl dimethyl ammonium chloride and diallyl diethyl ammonium bromide; substituted vinyl acetates, such as isopropenyl acetate and 1-methoxyvinyl acetate; allyl ethers having a poly(oxyalkylene) group, such as polyethylene glycol allyl ether, methoxypolyethylene glycol allyl ether, polypropylene glycol allyl ether, and polyethylene glycol-polypropylene glycol allyl ether; and the like.

[0056] In addition, the copolymerized modified polyvinyl alcohol resin may be a polyvinyl alcohol resin having a primary hydroxyl group in the side chain. Examples of such polyvinyl alcohol resins include a side chain 1,2-diol modified PVA resin obtained by copolymerizing 3,4-diacetoxy-1-butene, vinyl ethylene carbonate, glycerin monoallyl ether, etc.; a polyvinyl alcohol resin having a hydroxymethyl group in the side chain obtained by copolymerizing and saponifying hydroxymethyl vinylidene diacetate such as 1,3-diacetoxy-2-methylenepropane, 1,3-dipropionyloxy-2-methylenepropane, 1,3-dibutyronyloxy-2-methylenepropane, etc.

[0057] Methods for post-modification of the post-modified polyvinyl alcohol resin include methods of subjecting unmodified polyvinyl alcohol or the above-mentioned modified polyvinyl alcohol resin to acetoacetate esterification, acetalization, urethanization, etherification, grafting, phosphate esterification, oxyalkylenation, ester exchange reaction, etc. From the viewpoint of film flexibility, a caprolactone-modified polyvinyl alcohol resin by ester exchange reaction is more preferred.

[0058] The content of vinyl alcohol structural units contained in the polyvinyl alcohol resin is preferably 30 to 90 mol%. When the content of vinyl alcohol structural units is 30 mol% or more, the flexibility and bendability of the film are improved, and cracking and peeling during dicing of a thick film are suppressed. It is more preferably 32 mol% or more, even more preferably 35 mol% or more, and particularly preferably more than 46 mol%. On the other hand, when the content of vinyl alcohol structural units is 90 mol% or less, the dispersibility in organic solvents is good, the viscosity increase of the liquid is suppressed, and the appearance of the obtained film is better. It is more preferably 85 mol% or less, and particularly preferably 80 mol% or less.

[0059] The functional group contained in the polyvinyl alcohol resin is preferably an oxyalkylene group, an acetoacetyl group, a carboxyl group, or a sulfoxyl group, and from the viewpoint of film flexibility, it is more preferable that the polyvinyl alcohol resin contains an oxyalkylene group.

[0060] The average degree of polymerization of the polyvinyl alcohol resin is not particularly limited, but is preferably 200 to 2,000. When the average degree of polymerization is 200 or more, the flexibility and bendability of the film are further improved. On the other hand, when the average degree of polymerization is 2,000 or less, the dispersibility in an organic solvent is further improved.

[0061] The content of the polyvinyl alcohol-based resin is preferably more than 1 part by mass relative to 100 parts by mass of the total of the silica fine particles and the alkoxysilane hydrolysis condensate. The content of the polyvinyl alcohol-based resin is more preferably 1.5 parts by mass or more, more preferably 2.0 parts by mass or more, and particularly preferably 2.5 parts by mass or more. The upper limit is preferably 30 parts by mass or less, more preferably 25 parts by mass or less, and particularly preferably 20 parts by mass or less. When the content of the polyvinyl alcohol-based resin is 30 parts by mass or less, the haze of the film is low and the appearance is more excellent. When the content of the polyvinyl alcohol-based resin is low, the flexibility and bendability of the film are further improved, and film cracking during dicing of a thick film can be suppressed. The content of the polyvinyl alcohol-based resin is more preferably 5 parts by mass or more, more preferably 6 parts by mass or more, and particularly preferably 8 parts by mass or more. On the other hand, when the content is high, the dispersibility in an organic solvent is good, the viscosity increase of the liquid is suppressed, and the appearance of the obtained film is good.

[0062] [film] The film of the present invention can be a film made of the resin composition used in the present invention. The film of the present invention, particularly when used for optical applications, is generally used as a film formed by coating on a transparent substrate. This film is a porous film having a large number of pores. In addition, the surface of the film is preferably smooth, and the unevenness is preferably 5 nm or less, more preferably 3 nm or less, and particularly preferably 2 nm or less. The film of the present invention has excellent dicing properties when thick, low haze, and low refractive index, and therefore has high industrial utility value.

[0063] <Refractive index> The refractive index of the film of the present invention is usually 1.15 or more and 1.40 or less, and is appropriately selected according to the application. When used as an anti-reflection film for glass or plastic substrates, the refractive index is preferably 1.16 or more and 1.40 or less. When forming an anti-reflection film with a single layer, the minimum reflectance can be as close to 0% as possible by selecting the refractive index of the film according to the refractive index of the substrate. When used as a total reflection film, the refractive index is preferably 1.25 or less, more preferably 1.20 or less, and particularly preferably 1.18 or less. The lower the refractive index, the higher the proportion of light that is totally reflected at the interface between the transparent substrate and the film, which is preferable, but on the other hand, the porosity of the film increases, which may reduce the mechanical strength of the film.

[0064] <Structure> The structure of the film of the present invention is not particularly limited, and the pores are usually tunnel-shaped or interconnected pores in which independent pores are interconnected, but the detailed pore structure is also not particularly limited.In addition, the refractive index, dielectric constant, and density can be adjusted by adjusting the pore size and porosity, and by adjusting them, the film can be applied to various uses other than optical uses.The pore size and porosity can be adjusted by the composition of the film-forming coating liquid and the coating method described below.

[0065] The pore size of the film of the present invention is not particularly limited, but the pore size is usually preferably 0.1 to 50 nm, more preferably 1 to 20 nm, and particularly preferably 2 to 10 nm. If the pore size is too large, it is not suitable for an anti-reflection film formed of a thin film of, for example, about 100 nm, and defects may occur on the surface of the formed film, the surface unevenness may become large, and haze may become large due to light scattering, etc. In addition, there is a problem that the mechanical strength of the film is reduced due to the large number of defects.

[0066] The porosity of the film of the present invention is preferably 10 to 80%, more preferably 10 to 78%, more preferably 20 to 78%, more preferably 30 to 78%, and particularly preferably 30 to 70%. When the porosity is 10% or more, flexibility and optical properties are improved, while when it is 80% or less, mechanical strength, haze, and surface smoothness are improved.

[0067] The pore size of the membrane of the present invention can be measured by analyzing images observed with a transmission electron microscope (TEM) or a scanning electron microscope (SEM). The porosity of the membrane can be calculated from the relationship between the porosity and the refractive index according to the Lorentz-Lorentz equation.

[0068] The thickness of the film of the present invention is 1.5 to 10 μm. The thickness is more preferably 2.0 μm or more, and further preferably 3.0 μm or more. When the thickness is 1.5 μm or more, optical effects are exhibited. On the other hand, when the thickness is 10 μm or less, flexibility and haze are improved. More preferably, the thickness is 9 μm or less, and particularly preferably, the thickness is 8 μm or less. The thickness can be measured by the method described in the examples below.

[0069] The haze of the film of the present invention is preferably 0 to 3.0%. The haze is more preferably 2.5% or less, even more preferably 2.0% or less, even more preferably 1.8% or less, and particularly preferably 1.0% or less. When the haze is 3.0% or less, the optical properties become better. The lower limit is most preferably 0%. The haze can be measured by the method described in the examples below.

[0070] [Membrane manufacturing method] An example of the method for producing the membrane of the present invention will be described below, but the method for producing the membrane of the present invention is not limited to the following method.

[0071] To form the film of the present invention, a coating liquid for forming the film (corresponding to the resin composition used in the present invention containing a solvent and the like as appropriate; hereinafter also referred to as "film-forming coating liquid") is applied to a substrate, and the resulting wet film is then heated, dried, and cured.

[0072] The film-forming coating liquid is produced, for example, by adding silica fine particles and a hydrophilic resin to a silicate oligomer containing an alkoxysilane hydrolysis condensate. The coating liquid may also contain a solvent as appropriate.

[0073] (Method of producing coating solution for film formation) The film-forming coating liquid is produced by mixing a silicate oligomer containing an alkoxysilane hydrolysis condensate, silica fine particles, and a hydrophilic resin. The film-forming coating solution is adjusted to an appropriate concentration, taking into consideration the coatability when applied to a substrate, the thickness and smoothness of the coating film, etc. The concentration is adjusted by adding the above-mentioned hydrophilic solvent, and this concentration adjustment can be performed before or after mixing with the silica fine particles.

[0074] The silica fine particle concentration of the film-forming coating liquid is preferably 30% by mass or less, more preferably 25% by mass or less, particularly preferably 20% by mass or less, and most preferably 17% by mass or less. When the silica fine particle concentration is 30% by mass or less, the coating property is further improved and a film with surface smoothness is formed. On the other hand, from the viewpoint of the film formation efficiency of the film, the silica fine particle concentration of the film-forming coating liquid is preferably 1% by mass or more, more preferably 5% by mass or more.

[0075] The mixing ratio of the silicate oligomer containing an alkoxysilane hydrolysis condensate and the silica fine particles is not particularly limited as long as the pores of the film formed by using the resulting film-forming coating liquid are not blocked. If the ratio of silicate oligomer is too high, it becomes difficult to form pores during film formation, making it difficult to form a porous film with excellent optical performance.On the other hand, if the ratio of silicate oligomer is too low, the bonding between the silica fine particles becomes weak, resulting in insufficient mechanical strength and low adhesion to the substrate, which may cause damage or peeling depending on the post-processing or usage environment.

[0076] From this viewpoint, when mixing silicate oligomer containing an alkoxysilane hydrolysis condensate with silica fine particles, the mixing ratio of the silica fine particles to the alkoxysilane hydrolysis condensate is preferably silica fine particles:alkoxysilane hydrolysis condensate=1:0.01-2 (mass ratio), and more preferably 1:0.05-1 (mass ratio).

[0077] The content of the hydrophilic resin in the coating liquid for film formation is preferably 0.05% by mass or more, more preferably 0.1% by mass or more. When the content is 0.05% by mass or more, the flexibility and bendability of the film are further improved. On the other hand, the content is preferably 10% by mass or less, more preferably 5% by mass or less. When the content is 10% by mass or less, thickening of the liquid is suppressed, and the appearance of the obtained film is better.

[0078] The solvent contained in the coating liquid for film formation is water and / or an organic solvent. The solvent preferably contains a hydrophilic solvent, and the hydrophilic solvent is not particularly limited, but generally, alcohols such as methanol, ethanol, propanol, butanol, cellosolves such as ethyl cellosolve, butyl cellosolve, propyl cellosolve, glycols such as ethylene glycol, propylene glycol, hexylene glycol, etc. are used. These solvents may be used alone or in combination of two or more. These solvents may be derived from the dispersion of each raw material, or may be mixed when preparing the coating liquid for film formation.

[0079] [Laminate] A film made of the resin composition used in the present invention can be laminated on a substrate to form a laminate. Transparent substrates such as glass and plastics are used as the substrate to be laminated with the film. The transparent substrate has high light transmittance at a specific wavelength and is appropriately selected depending on the application using ultraviolet light, visible light, or infrared light. The specific wavelength is not limited to the visible light range, but in applications such as lenses, displays, solar cells, solar thermal power generation and other optical devices, building materials, and anti-reflective coatings for the interior and exterior of automobiles, it is preferable that the substrate has high transmittance for light with wavelengths in the visible light range. Usually, a substrate with a total light transmittance of 60% or more is used.

[0080] The thickness and shape of the substrate are not particularly limited, and the substrate may have scattering or haze, and may have fine irregularities on its surface, so long as they do not affect the performance of the film.

[0081] Examples of plastics that can be used to form the substrate include polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polycarbonate (PC), polyimide (PI), polymethyl methacrylate (PMMA), and cycloolefin polymer (COP).

[0082] The substrate surface may be either one that has been subjected to a surface modification treatment or one that has not been subjected to a surface modification treatment.

[0083] (Coating method) The method for laminating a film on a substrate is preferably a coating method, and examples of the coating method include dip coating, spin coating, die coating, spray coating, gravure coating, roll coating, curtain coating, screen printing, and inkjet printing.

[0084] (Drying / curing method) The wet film formed by applying the film-forming coating liquid to the substrate is dried to remove the solvent, and the drying temperature is usually 50 to 150° C., and a hot air dryer or the like is preferably used. The drying time is usually 1 to 10 minutes, and preferably 1 to 5 minutes.

[0085] When the transparent substrate is made of plastic, the drying temperature is usually 50 to 80°C, and the drying time is usually 1 to 10 minutes, preferably 1 to 5 minutes. In order to impart adhesion, a method of irradiating ultraviolet light in the presence of oxygen is recommended as the curing treatment after the drying. The ultraviolet light includes near ultraviolet light (near UV, wavelength 200 to 380 nm), far ultraviolet light (far UV, wavelength 10 to 200 nm), and extreme ultraviolet light (extreme UV, wavelength 1 to 10 nm), and usually far ultraviolet light is effective. Examples of ultraviolet light sources include low-pressure mercury lamps, high-pressure mercury lamps, excimer ultraviolet light (excimer UV) lamps, halide lamps, lasers, etc. The irradiation time of ultraviolet light is usually 1 second to 3 minutes. When the transparent substrate is made of glass, etc., the curing temperature is 80°C to 150°C, and a hot air dryer or the like is preferably used. The curing time is usually 1 minute to 60 minutes, preferably 1 minute to 30 minutes.

[0086] [Optical components] The optical member of the present invention may include the laminate of the present invention. The laminate itself may be an optical member, or the laminate may be used as a part of the optical member. Examples of the optical member of the present invention include a diffractive optical element (DOE), a cladding material such as an optical fiber, an optical waveguide, an optical display, an AR glass, a camera lens, a medical lens, a microlens, and a LiDAR.

[0087] The film of the present invention can be suitably used as an anti-reflection film, etc. The film of the present invention can be suitably used for displays, automobile panels, lighting fixtures, solar energy devices, camera lenses, face shields, glasses, optical waveguides, etc. As optical applications, it can be suitably used for diffractive optical elements (DOEs), cladding materials such as optical fibers, optical waveguides, optical displays, AR glasses, camera lenses, medical lenses, microlenses, LiDAR, etc. Furthermore, it can be suitably used as a member for improving the color and brightness of displays. EXAMPLES

[0088] The present invention will be described in detail below with reference to examples. However, the present invention can be modified appropriately without departing from the spirit of the present invention, and the present invention is not limited to the following examples.

[0089] In the examples, various physical properties were measured according to the following methods.

[0090] [Average primary particle size of silica particles] The average primary particle size of the silica fine particles was calculated by the BET method.

[0091] [Refractive index, film thickness] The refractive index and film thickness of the porous silicon oxide film laminate (1) were calculated from a reflectance spectrum obtained by an interference film thickness measurement device F20 manufactured by Filmetrics.

[0092] [Porosity] The porosity of the porous silicon oxide film laminate (1) was calculated from the relationship between the porosity and the refractive index according to the Lorentz-Lorentz equation. The refractive index of the silica particles was set to 1.46.

[0093] (Lorentz-Lorentz equation) Porosity (%) = (refractive index of silica particles - refractive index of porous silicon oxide film) / 0.46

[0094] [Hayes] The porous silicon oxide film laminate (2) was measured at room temperature using a spectrophotometer / haze meter ("COH7700" manufactured by Nippon Denshoku Industries Co., Ltd.).

[0095] [Dicing ability] The porous silicon oxide film laminate (2) was cut from the glass side at room temperature using a cutting machine equipped with a diamond cutting wheel (QCut150A manufactured by QATM). The cut cross section was observed using a FE-SEM (JSM-7900F manufactured by JEOL Ltd.), and the cut film surface was observed using a laser microscope (VK-9700 manufactured by Keyence Corporation), and evaluated according to the following criteria. (Crack) ○: No film cracks were observed in the cross section. ×: Film cracks were observed in the cross section. (Peeling evaluation method 1) ○: No peeling of the film was observed on the surface. ×: Film peeling was observed on the surface.

[0096] (Peeling evaluation method 2) The porous silicon oxide film laminate (2) was placed at room temperature, scratched from the glass side with a diamond cutter, and the film surface was manually broken along the scratch by applying equal force to both sides of the scratch. The film surface was observed with a laser microscope (Keyence Corporation, "VK-9700") and evaluated according to the following criteria. ○: No peeling of the film was observed on the surface. △: Partial peeling of the film was observed on the surface. ×: Peeling of the film was observed on the entire surface.

[0097] [Flexibility] The porous silicon oxide film laminate (3) was placed at room temperature and wrapped around a cylindrical metal rod with a diameter of 1 mm with the coating surface facing up, and the condition of the test piece was observed and evaluated according to the following criteria. ○: No cracks or peeling on the film ×: The film is cracked and the wrapped portion is peeled off.

[0098] [Production Example 1] Production of silicate oligomer (A) containing alkoxysilane hydrolysis condensate (1) Hydrolysis reaction process: In a 500mL jacketed reactor, 5 parts by mass of Shin-Etsu Silicone's product "KBM22" (dimethyldimethoxysilane content 99% by mass), 20 parts by mass of Mitsubishi Chemical's product "Silicate MS51" (average degree of polymerization n: 7, methyl silicate oligomer content 99.8% by mass), and 50 parts by mass of ethanol were charged, the upper limit reaction temperature was set to 40°C, and 33 parts by mass of 0.007% by mass hydrochloric acid aqueous solution was dropped over 10 minutes under stirring conditions. At this time, the reaction temperature rose by 5 to 10°C due to an exothermic reaction. Stirring was continued until the reaction temperature dropped by 5 to 10°C. The ratio of the hydrolyzable silane compound polymer to the total of the bifunctional hydrolyzable silane compound and the hydrolyzable silane compound polymer (the ratio of "Silicate MS51" to the total amount of "KBM22" and "Silicate MS51") was 80% by mass.

[0099] (2) Condensation reaction step: After the hydrochloric acid solution was added dropwise, the temperature was raised to 60° C. over 30 minutes under stirring conditions, and the temperature was maintained at 60° C. for 30 minutes. Then, the temperature was cooled to room temperature.

[0100] (3) Condensation reaction termination step: After cooling, 108 parts by mass of ethanol was added and stirred for 30 minutes to obtain 216 parts by mass of silicate oligomer (A) containing an alkoxysilane hydrolysis condensate. The concentration of the alkoxysilane hydrolysis condensate contained in the obtained silicate oligomer (A) containing an alkoxysilane hydrolysis condensate was 15% by mass, and the weight average molecular weight was 1949.

[0101] [Production Example 2] Production of silicate oligomer (B) containing alkoxysilane hydrolysis condensate To 100 parts by mass of the silicate oligomer (A) containing an alkoxysilane hydrolysis condensate, 50 parts by mass of ethanol was added and stirred for 30 minutes to obtain 150 parts by mass of the silicate oligomer (B) containing an alkoxysilane hydrolysis condensate.

[0102] [Production Example 3] Production of coating liquid (C) for forming porous silicon oxide film 97 parts by mass of chain silica fine particles (Nissan Chemical Industries, Ltd.'s product "Snowtex OUP", average primary particle diameter: 12 nm, average length: 40 to 100 nm, silica fine particle concentration 15 mass%) and 268 parts by mass of chain silica fine particles (Nissan Chemical Industries, Ltd.'s product "Organo Silica Sol MEK-ST-UP", average primary particle diameter: 12 nm, average length: 40 to 100 nm, silica fine particle concentration 20 mass%) were added to 150 parts by mass of silicate oligomer (B) containing an alkoxysilane hydrolysis condensate, and the mixture was stirred for 30 minutes to obtain 515 parts by mass of a coating liquid (C) for forming a porous silicon oxide film.

[0103] [Example 1] To 100 parts by mass of the coating liquid (C) for forming a porous silicon oxide film, 3.75 parts by mass of oxyalkylene group-modified polyvinyl alcohol ("GOHSENEX LW-200" manufactured by Mitsubishi Chemical Corporation, concentration 40% by mass, saponification degree 46-53 mol%, polymerization degree 200, melting point 150-230°C) was added, and the mixture was stirred for 30 minutes to produce 103.75 parts by mass of the coating liquid (D) for forming a porous silicon oxide film of the present invention. The coating liquid was applied to a glass substrate by a spin coater, and then dried to obtain a porous silicon oxide film laminate, which was used to evaluate the coating film. The results are shown in Tables 1 and 2.

[0104] [Example 2] Except for using 4.50 parts by mass of oxyalkylene group-modified polyvinyl alcohol ("GOHSENOL NK-05R" manufactured by Mitsubishi Chemical Corporation, concentration 10% by mass, saponification degree 71-75 mol%, polymerization degree 500), 104.50 parts by mass of the coating liquid for forming a porous silicon oxide film (D) was produced and evaluated in the same manner as in Example 1. The results are shown in Tables 1 and 2.

[0105] [Example 3] Except for changing the drying temperature of the porous silicon oxide film laminates (1) and (2) from 120° C. to 80° C., 103.75 parts by mass of the coating liquid (D) for forming a porous silicon oxide film was produced and evaluated in the same manner as in Example 1. The results are shown in Tables 1 and 2.

[0106] [Example 4] Except for changing the drying temperature of the porous silicon oxide film laminates (1) and (2) from 120° C. to 80° C., 104.50 parts by mass of the porous silicon oxide film-forming coating liquid (D) was produced and evaluated in the same manner as in Example 2. The results are shown in Tables 1 and 2.

[0107] [Comparative Example 1] Except for using 4.50 parts by mass of polyethylene glycol ("Polyethylene Glycol 200" manufactured by Fuji Film Wako Co., Ltd., concentration 10% by mass, freezing point -65 to -50°C), 104.50 parts by mass of the coating liquid for forming a porous silicon oxide film (D) was produced and evaluated in the same manner as in Example 1. The results are shown in Tables 1 and 2.

[0108] [Comparative Example 2] Except for using 4.50 parts by mass of polyethylene glycol ("Polyethylene Glycol 6,000" manufactured by Fuji Film Wako Co., Ltd., concentration 10% by mass, melting point 50 to 65°C), 104.50 parts by mass of the coating liquid for forming a porous silicon oxide film (D) was produced and evaluated in the same manner as in Example 1. The results are shown in Tables 1 and 2.

[0109] [Comparative Example 3] Except for using 4.50 parts by mass of polyethylene glycol ("Polyethylene Glycol 20,000" manufactured by Fuji Film Wako Co., Ltd., concentration 10% by mass, melting point 56 to 63°C), 104.50 parts by mass of the coating liquid for forming a porous silicon oxide film (D) was produced and evaluated in the same manner as in Example 1. The results are shown in Tables 1 and 2.

[0110] The following laminates were produced using the coating solutions of the above-mentioned Examples and Comparative Examples, and were evaluated.

[0111] [Preparation of porous silicon oxide film laminate (1) (for refractive index and porosity evaluation)] A 6-inch silicon wafer (manufactured by Advanced Materials Technology Corp.) was cut to a size of 2 cm, and a solution of the porous silicon oxide film-forming coating liquid obtained above, diluted 5 times with ethanol, was dropped onto the wafer, and the wafer was coated for 30 seconds at 2000 rpm with a spin coater ("MS-A150" manufactured by Mikasa Corp.) to produce a thin film.

[0112] Thereafter, the solvent was removed and the film was dried at 120°C for 10 minutes in a low-temperature thermostatic blower (manufactured by Yamato Scientific Co., Ltd.) to heat cure, thereby obtaining a laminate (1) of a porous silicon oxide film and a Si wafer having a thickness of 100 to 200 nm. The refractive index and porosity of the obtained porous silicon oxide laminate (1) were measured. The obtained evaluation results are shown in Tables 1 and 2.

[0113] [Preparation of porous silicon oxide film laminate (2) (for dicing and haze evaluation)] The coating liquid for forming the porous silicon oxide film obtained above was dropped onto a 1 mm thick slide glass plate ("S9111" manufactured by Matsunami Glass Co., Ltd.) and coated with a spin coater ("MS-A150" manufactured by Mikasa Co., Ltd.) at 2000 rpm for 30 seconds to produce a thin film.

[0114] Thereafter, the solvent was removed, and the laminate was placed in a low-temperature thermostatic blower (manufactured by Yamato Scientific Co., Ltd.) for thermal curing, and dried at 120°C for 10 minutes to obtain a laminate (2) of a porous silicon oxide film and a glass plate having a thickness of 4.5 μm. The dicing property and haze of the obtained porous silicon oxide laminate (2) were evaluated. The obtained evaluation results are shown in Tables 1 and 2.

[0115] [Preparation of porous silicon oxide film laminate (3) (for flexibility evaluation)] The porous silicon oxide film-forming coating liquid obtained above was dropped onto an acrylic sheet with a thickness of 0.3 mm (Technoloy S000, manufactured by Sumika Acrylic Sales Co., Ltd.), and coated with a spin coater (MS-A150, manufactured by Mikasa Co., Ltd.) at 2000 rpm for 30 seconds to produce a thin film. Thereafter, the solvent was removed, and the laminate was placed in a low-temperature thermostatic blower (manufactured by Yamato Scientific Co., Ltd.) for thermal curing, and dried at 70°C for 10 minutes to obtain a 4.5 μm-thick laminate (3) of a porous silicon oxide film and an acrylic sheet. The flexibility of the obtained porous silicon oxide laminate (3) was evaluated. The obtained evaluation results are shown in Tables 1 and 2.

[0116] [Table 1]

[0117] [Table 2]

[0118] It is seen that the films made of the resin compositions of Examples 1 to 4 have good dicing properties and refractive index when they are thick films. On the other hand, it is seen that the films made of the resin compositions of Comparative Examples 1 to 3 have high refractive index because the melting points of the hydrophilic resins are less than 80°C. [Industrial Applicability]

[0119] The porous silicon oxide film and laminate made of the resin composition used in the present invention can be suitably used for optical components such as diffractive optical elements (DOEs), cladding materials for optical fibers, optical waveguides, optical films, AR glasses, camera lenses, medical lenses, microlenses, LiDAR, etc. In particular, they can be effectively applied to applications requiring miniaturization and tracking of parts.

Claims

1. The film has a thickness of 1.5 to 10 μm and is made of a resin composition containing silica fine particles, an alkoxysilane hydrolysis condensate, and a hydrophilic resin having a melting point of 80° C. or higher.

2. The membrane of claim 1 , wherein the hydrophilic resin has a hydroxyl group.

3. The membrane according to claim 2 , wherein the content of hydroxyl groups directly bonded to the main chain of the hydrophilic resin is 35 mol % or less.

4. The film according to claim 1 , wherein the silica fine particles are chain-like silica fine particles.

5. The film according to claim 1, wherein the average primary particle diameter of the silica fine particles is 5 to 100 nm.

6. The film according to claim 1, wherein the alkoxysilane hydrolysis condensate has a weight average molecular weight of 1,000 to 5,000.

7. 2. The membrane according to claim 1, wherein the average degree of polymerization of the hydrophilic resin is from 200 to 2,000.

8. The membrane of claim 1 , wherein the hydrophilic resin is a polyvinyl alcohol-based resin.

9. The film according to claim 1 , wherein the content of the hydrophilic resin is more than 1 part by mass per 100 parts by mass of the total of the silica fine particles and the alkoxysilane hydrolysis condensate.

10. The film according to claim 1, wherein the content of the alkoxysilane hydrolysis condensate is 5 to 30 parts by mass relative to 100 parts by mass of the resin composition.

11. The film according to claim 1, wherein the content of the silica fine particles is 60 to 90 parts by mass based on 100 parts by mass of the resin composition.

12. The membrane of claim 1, having a porosity of 10 to 80%.

13. 2. The film of claim 1, having a refractive index of 1.15 to 1.

40.

14. The membrane of claim 1, wherein the pore size is from 0.1 to 50 nm.

15. A laminate comprising the film according to any one of claims 1 to 14 and a substrate.

16. 16. The laminate of claim 15, wherein the substrate is glass.

17. An optical member comprising the laminate according to claim 16 .

Citation Information

Patent Citations

  • Method for producing silicon oxide thin film-forming binder liquid and coating liquid

    JP2019023269A

  • Antifogging porous silicon oxide film and method for manufacturing the same

    JP2021182134A